Profitability performance analysis on Malaysian hotel industry during Covid-19 pandemic / Nur Hanisah Mohamad Said ... [et al.] - Mohamad Said, Nur Hanisah; Abdull Rahman, Nurul Labanihuda; Abd Mutalib, Hasyeilla; Badri Shah, Noor Sharida (Universiti Teknologi MARA, Negeri Sembilan, 2021)
The COVID-19 pandemic is becoming the worst worldwide and the increasing number of cases in Malaysia has impacted the tourism industry heavily, especially hotel businesses. The cancellation by travelling agencies due to the pandemic has affected various hotels. As a result, the companies had to shut down their businesses and stop operating as they failed to maintain their profits and they suffered losses. This study aims to examine the determinants of profitability in the hotel sectors in Malaysia from 2010 to 2019. The profitability level of the firms is evaluated using four different variables which are leverage, liquidity, net asset turnover, size of the company and panel data analysis techniques. The present study gathered data on hotels listed under Bursa Malaysia. The findings showed that the leverage and net asset turnover have a positive relationship with profitability while liquidity and size of a company have a negative relationship with profitability. The study also found that leverage and size of the company have a statistically significant relationship with profitability while liquidity and net asset turnover do not have a statistically significant relationship with profitability. This finding provides a better understanding for hotels to improve their financial performance and to have a better plan of their spending assets and leverage. Therefore, it can help the hotel sector to sustain and have recovery planning to prevent issues related to debt default payment in the future.